The Influence of Education Using Virtual Audiovisual Media on Pregnant Women's Knowledge About Covid 19 Prevention - Fakhriyah Fakhriyah; Mohammad Bakhriansyah; Meitria Syahadatina Noor; Andini Octaviana Putri (Faculty of Public Health, Sriwijaya University, 2022)
The emergence of coronavirus infections has resulted in an epidemic that is rapidly developing into one of the most significant public health threats in recent times. Maternal health services cannot be separated from being affected both in terms of access and quality. Pregnant women must be aware of the risk of contracting COVID-19 because have higher risk of the morbidity and mortality rates. The purpose of this study is to analyze the influence of online counseling on pregnant women's knowledge about COVID-19 prevention. This study used a quasi-experimental design with one group pretest-posttest design. The research location is in the Banjar Regency and Banjarbaru. The population is all pregnant women who visited the Poskesdes in Banjar Regency and the PMB in Banjarbaru as many as 66 people. Counseling is done online with audiovisual media. Samples was 46 people who were taken by purposive sampling. The independent variable is counseling about COVID-19 prevention and the dependent is knowledge. The method of data analysis is the Wilcoxon test. The intervention was carried out using google meet. Pre and post-tests were carried out to measure knowledge. The results of this study were that there was a significant difference in the knowledge of pregnant women before and after receiving counseling (df=46, p=0.0001). The conclusion of this study is counseling using audiovisuals can increase pregnant women's knowledge about the prevention of COVID-19. Education about COVID-19 prevention can virtually be implemented in comprehensive maternal and child health services as an effort to prevent and control COVID-19.